CRISPR/Cas9-editing of PRNP in Alpine goats - Aurélie Allais-Bonnet; Christophe Richard; Marjolaine André; Valérie Gelin; Marie-Christine Deloche; Aurore Lamadon; Gwendoline Morin; Béatrice Mandon-Pépin; Eugénie Canon; Dominique Thépot; Johann Laubier; Katayoun Moazami-Goudarzi; et al. (Veterinary Research)
Abstract Misfolding of the cellular PrP (PrPc) protein causes prion disease, leading to neurodegenerative disorders in numerous mammalian species, including goats. A lack of PrPc induces complete resistance to prion disease. The aim of this work was to engineer Alpine goats carrying knockout (KO) alleles of PRNP, the PrPc-encoding gene, using CRISPR/Cas9-ribonucleoproteins and single-stranded donor oligonucleotides. The targeted region preceded the PRNP Ter mutation previously described in Norwegian goats. Genome editors were injected under the zona pellucida prior to the electroporation of 565 Alpine goat embryos/oocytes. A total of 122 two-cell-stage embryos were transferred to 46 hormonally synchronized recipient goats. Six of the goats remained pregnant and naturally gave birth to 10 offspring. Among the 10 newborns, eight founder animals carrying PRNP genome-edited alleles were obtained. Eight different mutated alleles were observed, including five inducing KO mutations. Three founders carried only genome-edited alleles and were phenotypically indistinguishable from their wild-type counterparts. Among them, one male carrying a one base pair insertion leading to a KO allele is currently used to rapidly extend a PRNP-KO line of Alpine goats for future characterization. In addition to KO alleles, a PRNP del6 genetic variant has been identified in one-third of founder animals. This new variant will be tested for its potential properties with respect to prion disease. Future studies will also evaluate the effects of genetic background on other characters associated with PRNP KO, as previously described in the Norwegian breed or other species.